Strumienie przychodów finansowych w rolniczych gospodarstwach domowych na terenie Warmii i Mazur - Kucka, Elżbieta; Stempel, Ryszard (Streams of Financial Incomes in Households of Farmers in Warmia and Mazury, 2005)
The aim of the research is to gather data with the help of an interview with users of 150 farms about real payments connected with possessing a farm and a household at the beginning and end of 2003. The article tries to answer the questions concerning the level of income diversification depending on a possessed area of farmlands as well as sources, and structure of incomes in farmers' households.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 519-524